Culinary Tourism as A Place and Product Branding. Case Study: Batu Jamus Rubber Plantation in Karanganyar, Central of Java - Erni Setyowati; Anggana Fitri Satwikasari (International Journal of Built Environment and Scientific Research, 2017)
Rubber plantation of Batujamus, the largest plantation in Central Java Province and Tourism region of Sukuh Temple in Karanganyar regency, Central Java Province is taken as a case to focus discussion on the meaning of "A Place and Product Branding". This study aims to describe the concept of sustainable agro tourism with narrative description based on the consideration of "Finding a place and Product Branding Strategy". By using Multi-dimensional Scale of SPSS and Factor Analysis, this research found out that the desire to stay in a comfortable and green areas and the nearness to hinduism religion temple as the reason why they prefer the Rubber Plantation of Batujamus as a temporary shelter when they visit it.